RESTful Web Services with Dropwizard : Over 20 Recipes to Help You Build High-Performance, Production-Ready RESTful JVM-Based Backend Services /: Over 20 Recipes to Help You Build High-Performance, Production-Ready RESTful JVM-Based Backend Services. (2014) - Unknown
No abstract available